2011
DOI: 10.1590/s1807-59322011000400022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic periodontitis decreases serum prohepcidin levels in patients with chronic kidney disease

Abstract: OBJECTIVE:To determine the impact of periodontal treatment on serum levels of prohepcidin (the prohormone of hepcidin) and systemic inflammation markers, as well as correlations among these markers, in patients with chronic periodontitis and chronic kidney disease who were not undergoing dialysis.METHODS:We included 56 chronic periodontitis patients, 36 with chronic kidney disease and 20 without systemic diseases and with normal renal function (control group). Chronic kidney disease was defined as suggested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 27 publications
5
77
0
2
Order By: Relevance
“…Chronic PD, a bacterial infection of the toothsupporting tissues, and which is found in the subgingival plaque, may lead to increased CRP and IL-6 serum levels, which decrease, along with clinical markers of the disease, after treatment. 14,19,22 Therefore, chronic PD also contributes to this low-grade inflammation, with exposure to oxidative stress, through increased levels of oxygen-reactive species and decreased Our results are worrying. The high prevalence of PD in the general population, 2 its association with CKD, 4 and the greater severity of PD in CKD patients 13 all point to the importance of immediate referral of CKD patients with a diagnosis of PD to dental treatment, a practice that does not seem to be frequent among the professionals directly caring for these patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Chronic PD, a bacterial infection of the toothsupporting tissues, and which is found in the subgingival plaque, may lead to increased CRP and IL-6 serum levels, which decrease, along with clinical markers of the disease, after treatment. 14,19,22 Therefore, chronic PD also contributes to this low-grade inflammation, with exposure to oxidative stress, through increased levels of oxygen-reactive species and decreased Our results are worrying. The high prevalence of PD in the general population, 2 its association with CKD, 4 and the greater severity of PD in CKD patients 13 all point to the importance of immediate referral of CKD patients with a diagnosis of PD to dental treatment, a practice that does not seem to be frequent among the professionals directly caring for these patients.…”
Section: Discussionmentioning
confidence: 78%
“…12 CKD patients have more severe PD compared with the PD of patients without a systemic disease. 13 Compared to individuals without systemic diseases and PD, CKD patients have higher levels of traditional systemic inflammatory markers (IL-6 and C-reactive protein) and of pro-hepcidin (the pro-hormone form of hepcidin, the main regulator of iron homeostasis), 14 which, along with parameters of clinical severity, level of clinical insertion and probing depth, decrease after PD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We found the significant positive correlation between hs-CRP and periodontal status and significantly decreased inflammatory marker in the next 8 weeks after completion of periodontal therapy. Vilela et al 49 also reported the reduction of prohepcidin, IL-6, and hs-CRP in both chronic kidney disease and control patients following periodontal treatment. This study differed from previous reports that demonstrated significant reduction of inflammation in the next 12 weeks after completion of therapy.…”
Section: Discussionmentioning
confidence: 94%
“…The results concluded that patients undergoing periodontal treatment experience perturbations of systemic inflamma tion of a greater magnitude after nonsurgical than surgical periodontal therapy. Viela M et al 30 reported the effect of periodontal treatment in patients with CKD and found that the treatment resulted in significant reductions in Creactive protein, interleukin6, and prohepcidin levels before and 3 months after treatment. The study concluded that successful periodontal treatment may represent an important means of ameliorating the inflammatory burden seen in CKD.…”
Section: Resultsmentioning
confidence: 99%